STRUCTURAL DEFORMATION OF TUNGSTEN DISELENIDE NANOSTRUCTURES INDUCED BY OZONE OXIDATION AND INVESTIGATION OF ELECTRONIC PROPERTIES CHANGE - Kim, Eunjeong; Lee, Sangyoeb; Je, Yeonjin; Lee, Dong Park; Park, Sang Jun; Jeong, Sanghyun; Park, Joon Sik; Ahn, Byungmin; Park, Jun Hong (Archives of Metallurgy and Materials, 2022)
Tungsten diselenide (WSe2) is one of the promising transition metal dichalcogenides (TMDs) for nanoelectronics and optoelectronics. To enhance and tune the electronic performance of TMDs, chemical functionalization via covalent and van der Waals approaches has been suggested. In the present report, the electric and structural transition of WSe2 oxidized by exposure to O3 is investigated using scanning tunneling microscopy. It is demonstrated that the exposure of WSe2/high-ordered pyrolytic graphite sample to O3 induces the formation of molecular adsorbates on the surface, which enables to increase in the density of states near the valence band edge, resulting from electric structural modification of domain boundaries via exposure of atomic O. According to the work function extracted by Kelvin probe force microscopy, monolayer WSe2 with the O3 exposure results in a gradual increase in work function as the exposure to O3. Therefore, the present report demonstrates the potential pathway for the chemical functionalization of TMDs to enhance the electric performance of TMDs devices.
Keywords: Chemical functionalization; Dichalcogenides; Domain boundary; Electronic performance; Ozone oxidation; Property changes; Pyrolytic graphite; Structural deformation; Structural transitions; Van der Waal; Domain Boundary; Ozone Oxidation; Scanning Tunneling Microscopy; Structural Deformation; Tungsten diselenide